Truth is Stranger than Science Fiction: The Quest for Knowledge in Andrei Tarkovskii’s Solaris and Stalker - Thomas McLenachan (Slovo, 2014)
This article explores Andrei Tarkovskii’s conception of truth in Solaris (1972) and Stalker (1979) as part of his wider philosophical project concerning knowledge. The director’s epistemological views form a core dimension of his life and aesthetic as he strives towards what he considers a higher, spiritual ‘idea of knowing’. In his search for this idealised notion of truth, Tarkovskii uses the medium of film to address what he perceives as a profound imbalance in modern civilization between scientific rationalism and spiritual/aesthetic ‘truth’. This is nowhere more prominent than in his two science fiction films, Solaris and Stalker, as he uses the genre as a battleground to discuss key debates in epistemology. Comparisons will be made with the Russian author and thinker Tarkovskii most revered, Fyodor Dostoevskii, and the Soviet-period science fiction authors whose works he adapted, Stanisław Lem and the Strugatskii brothers, in order to elucidate how the director came to cinematically represent his philosophy. Click here to read article